Industrial Property Rights and the Phenomenon of Counterfeiting in Algeria: Case Study of Tlemcen and Oran - Hirech , Nawal (Finance and Business Economies Review, 2023)
The protection of industrial property rights is fundamental to economic growth in general, as it makes it possible to combat the counterfeiting that plagues a large number of economies throughout the world. The aim of this study is to ascertain the effectiveness of the Algerian industrial property rights protection system through a survey of entrepreneurs in the manufacturing sector in the Oran and Tlemcen regions. This study provides an insight into the degree of satisfaction of entrepreneurs with this system, as well as identifying the reasons for the development of counterfeiting in Algeria in the manufacturing sector, which can ultimately be explained more by a lack of willingness to protect on the part of Algerian entrepreneurs than by the failure of the industrial property rights protection system.